The Comparative Study of Chinese and Western Cultural Heritage Management Based on Cultural Perspective - Yi , Luan; Vanitwatthananuwat, Chaiyot (Journal of Roi Kaensarn Academi, 2025)
From the perspective of culture, this paper compares the similarities and differences between Chinese and western cultural heritage management, and sorts out the cultural heritage management under the influence of Chinese and Western culture. The main objectives of this study are as follows: First, compare the similarities and differences of Chinese and Western heritage management, starting from the concept, compare the essential differences in order to better understand themselves and explore the experience that can be used for reference; Second, how are the management mechanisms of cultural heritage different between China and the west? Cultural theory and cross-cultural theory are applied to all levels of cultural heritage management, trying to analyze the cultural value embodied by heritage and the profound impact of cultural heritage on heritage management. The comparison between Chinese and Western cultural heritage management can be divided into two aspects: horizontal and vertical. Horizontal comparison can be divided into static comparison and dynamic comparison, that is, static comparison between Chinese and western management systems and cross-cultural communication in heritage management. The longitudinal comparison is to compare the development stages of Chinese and Western heritage management. The horizontal proportion of heritage management is divided into three parts: main body, client cultural heritage and intermediary management system. Thirdly, the management of Chinese and Western cultural heritage should take its essence and discard its dross.